Nilai Tambah, Keuntungan, Gula, ANALISIS NILAI TAMBAH PRODUK HASIL OLAHAN AREN: ABSTRAK, PENDAHULUAN, METODOLOGI PENELITIAN, HASIL DAN PEMBAHASAN. KESIMPULAN, SARAN, UCAPAN TERIMAKASIH, DAFTAR PUSTAKA - Roudotul Janah, Nabila; Muhammad Nu'man Adinasa (Universitas Garut, 2024)
The aim of this research is to analyze the added value of processing palm-based products, namely brown sugar, broom palm fiber and ant sugar, by examining aspects of production costs, labor and profits obtained from each type of processing. The method used in determining the location is purposive sampling. The research data analysis used primary and secondary data analysis, primary data resulting from the interview process with sugar palm processors and secondary data obtained from related installations such as BPS and the Department of Agriculture. The sampling technique in this research used purposive sampling with the sample criteria being farmers who processed sugar palm. This research uses the value added ratio method, which measures the ratio between raw material costs, output produced, and the contribution of labor to production. The research results show that processing ant sugar produces the highest added value, with a profit ratio reaching 80%, followed by brown sugar with a profit margin of 83%, and broom palm fiber with a profit margin of 59%. The raw material costs for ant sugar are higher, but this product also has a higher selling value, even though the profit margin is lower. On the other hand, processing brown sugar is more profitable because raw material costs are lower with a high production process. Fiber broom production, using cheap raw materials, requires more manual skills, resulting in lower profits.Keywords : Added Value, Profit, Sugar, Palm Oil Broom.